Voxel‐based morphometric magnetic resonance imaging (MRI) postprocessing in MRI‐negative epilepsies. Issue 6 (23rd April 2015) - Wang, Z. Irene; Jones, Stephen E.; Jaisani, Zeenat; Najm, Imad M.; Prayson, Richard A.; Burgess, Richard C.; Krishnan, Balu; Ristic, Aleksandar; Wong, Chong H.; Bingaman, William; Gonzalez‐Martinez, Jorge A.; Alexopoulos, Andreas V.
Abstract : Objective: In the presurgical workup of magnetic resonance imaging (MRI)‐negative (MRI − or "nonlesional") pharmacoresistant focal epilepsy (PFE) patients, discovering a previously undetected lesion can drastically change the evaluation and likely improve surgical outcome. Our study utilizes a voxel‐based MRI postprocessing technique, implemented in a morphometric analysis program (MAP), to facilitate detection of subtle abnormalities in a consecutive cohort of MRI − surgical candidates. Methods: Included in this retrospective study was a consecutive cohort of 150 MRI − surgical patients. MAP was performed on T1‐weighted MRI, with comparison to a scanner‐specific normal database. Review and analysis of MAP were performed blinded to patients' clinical information. The pertinence of MAP + areas was confirmed by surgical outcome and pathology. Results: MAP showed a 43% positive rate, sensitivity of 0.9, and specificity of 0.67. Overall, patients with the MAP + region completely resected had the best seizure outcomes, followed by the MAP − patients, and patients who had no/partial resection of the MAP + region had the worst outcome ( p < 0.001). Subgroup analysis revealed that visually identified subtle findings are more likely correct if also MAP + . False‐positive rate in 52 normal controls was 2%. Surgical pathology of the resected MAP + areas contained mainly non–balloon‐cell focal cortical dysplasia (FCD). Multiple MAP + regions were present in 7% of patients. Interpretation: MAP can be a practical and valuable tool to: (1) guide the search for subtle MRI abnormalities and (2) confirm visually identified questionable abnormalities in patients with PFE due to suspected FCD. A MAP + region, when concordant with the patient's electroclinical presentation, should provide a legitimate target for surgical exploration. Ann Neurol 2015;77:1060–1075